BALIGRAFI DIGUNAKAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS AKSARA BALI - Ni Wayan Sugiani; Putu Purnami , Ida Ayu; Sukma Wirani, Ida Ayu (STKIP Subang, 2026)
This research was conducted with the aim to (1) explain how the learning process carried out by the teacher in Baligrafi is used to improve the Balinese script writing skills of 10th grade students of SMA Negeri 1 Baturiti. (2) find out how creating Baligrafi can improve the Balinese script writing skills of 10th grade students of SMA Negeri 1 Baturiti. (3) understand students' opinions regarding learning by implementing Baligrafi as a project. The subjects in this study were the 10th grade students of SMA Negeri 1 Baturiti, and the object was Baligrafi as a project in learning. The methods used to collect and analyze data were qualitative descriptive techniques, quantitative descriptive techniques, and questionnaires, with the research results as follows: (1) there was an increase in students' understanding of the Balinese script learning material. (2) through Baligrafi, there was an improvement in students' skills in writing Balinese script. (3) there is an increase in student responses and student enthusiasm to learn Balinese script using Baligrafi. The implication of this research is that teachers can develop models related to creativity that are preferred or liked by students.